HLA-DM stabilizes the empty MHCII binding groove: a model using customized Natural Move Monte Carlo - Demharter, S; Knapp, B; Deane, C; Minary, P (American Chemical Society, 2019)
MHC class II molecules bind peptides derived from extracellular proteins that have been ingested by antigen-presenting cells and display them to the immune system. Peptide loading occurs within the antigen-presenting cell and is facilitated by HLA-DM. HLA-DM stabilises the open conformation of the MHCII binding groove when no peptide is bound. While a structure of the MHCII/HLA-DM complex exists, the mechanism of stabilisation is still largely unknown. Here, we applied customised Natural Move Monte Carlo to investigate this interaction. We found a possible long range mechanism that implicates the configuration of the membrane-proximal globular domains in stabilising the open state of the empty MHCII binding groove.